Analisis Efisiensi Termoelektrik, Tantangan Pengembangan, dan Faktor-faktor yang Mempengaruhi Efek Seebeck - Ginting, Canda Lesmana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Abstract: Thermoelectric technology offers an innovative solution for converting heat energy into electricity through the Seebeck Effect. However, its conversion efficiency remains a major challenge in its development. This study aims to analyze various factors affecting thermoelectric performance, including materials, temperature differences, electrical and thermal conductivity, and system design optimization. A literature review reveals that materials based on bismuth telluride (Bi₂Te₃), lead telluride (PbTe), and nanocomposites have great potential to enhance the figure of merit (zT). Furthermore, integrating thermoelectric systems with renewable energy sources, such as solar and geothermal energy, can improve energy conversion efficiency. The main challenges in implementing this technology include high production costs, material limitations, and material degradation due to repeated thermal cycles. Therefore, research focuses on developing new materials, optimizing module designs, and improving manufacturing techniques to enhance the reliability and durability of thermoelectric systems. With ongoing advancements in this field, thermoelectric technology is expected to become a sustainable solution for utilizing waste heat energy and supporting the transition to green energy. Keywords : Thermoelectric, Seebeck Effect, energy conversion, thermoelectric materials, efficiency